Growth Light Environment Changes the Sensitivity of Photosystem I Photoinhibition Depending on Common Wheat Cultivars - Takagi, Daisuke; Ihara, Hiroaki; Takumi, Shigeo; Miyake, Chikahiro (Frontiers in Plant Science, 2019)
Light is an important factor for determining photosynthetic performance in land plants. At high light intensity, land plants develop photosynthetic activity by increasing electron sinks, such as Calvin cycle and photorespiration and photoprotective mechanisms in photosystem II (PSII), to effectively utilize light and protect them from photoinhibition. In addition to PSII, photosystem I (PSI) has a risk of undergoing photoinhibition under high light intensity because of the reactive oxygen species (ROS) produced within PSI. However, the acclimation response has hardly been evaluated in the relationship of PSI photoprotection to growth light. In this study, we studied the effect of growth light intensity on the photoprotective mechanisms in PSI using six wheat cultivars. To evaluate the susceptibility of PSI to its photoinhibition, we used the repetitive short-pulse (rSP) illumination method to cause O2-dependent PSI photoinhibition. We found that PSI photoinhibition induced by rSP illumination was much more alleviated in wheat cultivars grown under high-light conditions compared to those grown under low-light conditions. Here, we observed that wheat plant grown under high-light conditions lowered the susceptibility of PSI to its photoinhibition compared to those grown under low-light conditions. Furthermore, the acclimation response toward PSI photoinhibition was significantly different among the studied wheat cultivars, although the quantum yields both of PSII and PSI were increased by high-light acclimation in all wheat cultivars as reported previously. Interestingly, we observed that total chlorophyll content in leaves correlated with the susceptibility of PSI to its photoinhibition. On the basis of these results, we suggest that high-light acclimation induces protection mechanisms against PSI photoinhibition in land plants, and the increase in the leaf chlorophyll content relates to the susceptibility of PSI photoinhibition in wheat plants.